(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objective: The aim of this study was to investigate causal association of serum ferritin with pre-term labour. Materials and Methods: This is a case-control study done on one hundred and twenty women from July 2005 to June 2007 in the department of obstetrics and gynecology of Bangabandhu Sheikh Mujib Medical University (BSMMU) and Mother and Child Health Training Institute (MCHTI), Azimpur, Dhaka. Cases (n=60) were singleton pregnant women starting preterm labour within 28-36 weeks of pregnancy and control (n=60) were singleton pregnant women of >37 weeks of gestation who were in lalour. In this case-control study pre-term labour patients were compared with controls regarding their serum ferritin level. Result: Mean ±SD serum ferritin level of control and in pre-term labour group of women were 37.01±26.84 μg/L was 210.37±67.20 μg/L respectively. The difference between two groups was statistically highly significant (<0.001) Key words: Preterm lalour; serum ferritin DOI: 10.3329/bjog.v24i1.6321 Bangladesh J Obstet Gynaecol, 2009; Vol. 24(1) : 14-17